The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/bmjopen-2018-025186
|View full text |Cite
|
Sign up to set email alerts
|

Advice on healthy pregnancy, delivery, motherhood and information on non-communicable diseases in the maternal care programme in Myanmar: a cross-sectional study

Abstract: ObjectivePregnancy and delivery periods offer an opportunity for counselling women to improve behavioural risk and prevent complications, including non-communicable diseases (NCDs). However, little evidence is available on counselling offered during antenatal and postnatal care (PNC) in Myanmar. This study aimed to assess the contents of advice and information received by women during antenatal and postnatal counselling and to identify factors associated with receiving those advice and information.DesignCross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The WHO guidelines included four major areas; umbilical cord care (to prevent infection), early initiation and exclusive breastfeeding, thermoregulation measures, and early recognition of danger signs. [2,3] In Kayonza District, where the study was conducted, the 35% neonatal mortality rate is much higher than in other eastern province districts. The high mortality rate is in line with their low rate of neonatal checkups (2%) in the first two days following birth.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The WHO guidelines included four major areas; umbilical cord care (to prevent infection), early initiation and exclusive breastfeeding, thermoregulation measures, and early recognition of danger signs. [2,3] In Kayonza District, where the study was conducted, the 35% neonatal mortality rate is much higher than in other eastern province districts. The high mortality rate is in line with their low rate of neonatal checkups (2%) in the first two days following birth.…”
mentioning
confidence: 94%
“…According to the literature, maternal roles and the magnitude of ENC knowledge and practice are vitally needed. [3] In Rwanda, the 2015 National Institute of Statistics Rwanda (NISR) reported that 85% of neonatal deaths are the result of prematurity, sepsis, asphyxia, poor management of pregnancy and delivery complications, and poor quality of care immediately following the birth. [4] Many of these neonatal deaths could be prevented if mothers used the evidenced-based ENC guidelines.…”
mentioning
confidence: 99%
“…Anaemia is one of the major public health problems globally and the second leading cause of disability among pregnant women (World Health Organization, 2016). Poor maternal health is also associated with low birth outcomes including maternal morbidity and mortality (Okawa et al, 2019). Anaemia is defined as less than 12.0g/dl for non-pregnant and 11.0g/dl haemoglobin level for pregnant women (Ministry of Health et al, 2017) however definition varies in terms of severity, sex, living condition, and status of women including age (Ford et al, 2020;Miles et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrate that maternal morbidity and mortality rates are higher for those women who do not receive ANC 7 . Timely and appropriate ANC improves birth outcomes through proper delivery of quality health services which includes physical examinations, health screenings, counselling, prevention of complications, and even treatment of health problems 8 . Mothers are vulnerable during pregnancy due to many complications which are preventable.…”
Section: Introductionmentioning
confidence: 99%